ENDOSCOPIC TREATMENT OF CICATRICAL TRACHEAL STENOSES - E. A. Drobyazgin; Yu. V. Chikinev; M. S. Anikina; I. E. Sudovikh (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to evaluate the results of endoscopic treatment of cicatrical tracheal stenoses.MATERIAL AND METHODS. During the period from 1995 to 2018, 145 patients with cicatrical tracheal stenoses (men – 102, women – 43) aged 15 to 83 years were treated in the clinic. Stenosis was post tracheostomy in 96 patients, postintubation in 39 patients, after circular tracheal resection in 6 patients, after tracheolaryngoplasty in 3 patients, after radiation therapy for primary tracheal cancer in 1 patient. Endoscopic treatment was performed in 136 patients.RESULTS. In the tracheal dilation, only 42 (30,88 %) patients managed to achieve stabilization of the lumen of the trachea. Stenting of the narrowed part of the trachea with stent type Dumon was in 62 (45,58 %) patients due to restenosis. Formation of the lumen sufficient for breathing was possible in 40 (70,2 %) patients. All the complications that occurred during the stent in the trachea were diagnosed and eliminated.CONCLUSION. Endoscopic methods of treatment of patients with cicatrical tracheal stenoses were highly effective allowing to restore and maintain airway patency, both temporarily (for the purpose of preoperative preparation) and constantly.The authors declare no conflict of interest.The authors confirm that they respect the rights of the people participated in the study, including obtaining informed consent when it is necessary, and the rules of treatment of animals when they are used in the study. Author Guidelines contains the detailed information.